THE EFFECT OF EASE, TRUST AND SECURITY ON INTEREST IN USING GOPAY ON THE GOJEK APPLICATION (Case Study Of Society In The Lippo Cikarang) - Marbun, Yuli Fransiska; Sautman Sinaga; Poerwaningsih (Fundamental Management Journal, 2021)
Currently experiencing increasingly rapid technological developments, which have influenced the current economic development. In this modern era, technological developments have made changes where the current payment system has shifted cash into a non-cash payment instrument, its development has further increased. This research is quantitative in nature, the sample was taken in the study, namely the Lippo Cikarang society of respondents as many as 100, to measure interest using Gopay, namely the F test, T test, R2 (coefficient of determination) used. And variables used in this research are ease, trust, security. Keywords : ease, trust, security, interest in using, Gopay